2019
DOI: 10.1111/codi.14545
|View full text |Cite
|
Sign up to set email alerts
|

A propensity‐score‐matched analysis of laparoscopic vs open surgery for rectal cancer in a population‐based study

Abstract: Aim The oncological risk/benefit trade‐off for laparoscopy in rectal cancer is controversial. Our aim was to compare laparoscopic vs open surgery for resection of rectal cancer, using unselected data from the public healthcare system of Catalonia (Spain). Methods This was a multicentre retrospective cohort study of all patients who had surgery with curative intent for primary rectal cancer at Catalonian public hospitals from 2011 to 2012. We obtained follow‐up data for up to 5 years. To minimize the difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 42 publications
2
8
0
1
Order By: Relevance
“…Draeger et al [31] compared LAP and OPEN in a regional German registry‐based cohort comprising more than 1500 rectal cancer patients operated on from 2004 to 2013, and found that overall survival and cancer‐specific survival was higher in the LAP group. In a registry‐based study from Spain, Manchon‐Walsh et al [32] also compared more than 1500 rectal cancer patients undergoing LAP or OPEN surgery during 2011–2012 using propensity score matching, and found that LAP patients had better overall and cancer‐specific survival as well as fewer local recurrences.…”
Section: Discussionmentioning
confidence: 99%
“…Draeger et al [31] compared LAP and OPEN in a regional German registry‐based cohort comprising more than 1500 rectal cancer patients operated on from 2004 to 2013, and found that overall survival and cancer‐specific survival was higher in the LAP group. In a registry‐based study from Spain, Manchon‐Walsh et al [32] also compared more than 1500 rectal cancer patients undergoing LAP or OPEN surgery during 2011–2012 using propensity score matching, and found that LAP patients had better overall and cancer‐specific survival as well as fewer local recurrences.…”
Section: Discussionmentioning
confidence: 99%
“…A recent propensity-matched analysis including T4 tumours showed a 2-year DFS of 64.9% for stage III patients in the laparoscopic group. [6] Oncological outcomes of randomized control trials comparing R-TME vs. L-TME have not been published yet. However, previous descriptive studies showed equivalence in terms on DFS and OS.…”
Section: 8%)[2]mentioning
confidence: 99%
“…In COLOR II trial, patients with stage III operated laparoscopically showed better rate of DFS than the open surgery group with a difference of 12.9% [ 6 ]. A recent Spanish population-based study comparing laparoscopic with open surgery that included 1359 patients showed that laparoscopy was an independent factor for better LR and long-term OS rates in rectal cancer [ 21 ]. Other published population-based studies with long-term follow-up reported that the laparoscopic approach had better oncological outcomes than the open surgery [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%